2001
DOI: 10.1089/104303401450924
|View full text |Cite
|
Sign up to set email alerts
|

Retrovector Encoding a Green Fluorescent Protein–Herpes Simplex Virus Thymidine Kinase Fusion Protein Serves as a Versatile Suicide/Reporter for Cell and Gene Therapy Applications

Abstract: Expression vectors encoding herpes simplex virus thymidine kinase (HSVTK) have been extensively used in cell and gene therapy applications either as anticancer "suicide" or as "self-destruct" transgenes in adoptive immunotherapy applications. In both gene therapy applications, reliable detection of HSVTK transgene expression is required in genetically engineered cells. Direct fluorescent labeling of the HSVTK protein may be the remedy. We designed a retrovector encoding a chimeric GFP-HSVTK fusion protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…One hundred percent of eGFP-expressing cells were positive for HSV by immunohistochemistry. Of the fluorescence-activated cell sorted cells that did not express eGFP, none were positive for HSV by immunohistochemistry, except for Ͻ1% of cells infected at a MOI of 1 at 24 h. This finding supports the argument that eGFP is an accurate marker of HSV infection (45,46). This was also confirmed in an in vivo model, in which we administered NV1066 i.p.…”
Section: Mechanism Of Induction Of Apoptosissupporting
confidence: 82%
“…One hundred percent of eGFP-expressing cells were positive for HSV by immunohistochemistry. Of the fluorescence-activated cell sorted cells that did not express eGFP, none were positive for HSV by immunohistochemistry, except for Ͻ1% of cells infected at a MOI of 1 at 24 h. This finding supports the argument that eGFP is an accurate marker of HSV infection (45,46). This was also confirmed in an in vivo model, in which we administered NV1066 i.p.…”
Section: Mechanism Of Induction Of Apoptosissupporting
confidence: 82%
“…The retrovirus used in this study is a MMLVderived retrovirus vector produced by the 293-GPG packaging cell line (39). This cell line, a generous gift from J. Galipeau (Lady Davis Institute for Medical Research, Montreal, QC, Canada), generates a VSV-G-pseudotyped retrovirus vector encoding a fusion protein between the herpes simplex virus thymidine kinase (TK) protein and the green fluorescent protein (48). Suspension-adapted cell cultures were maintained in calcium-free Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum (HyClone, Logan, UT) and tetracycline (1 g/ml; Fisher Scientific, Nepean, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…NV1066 carries such a marker gene, a constitutively expressed transgene for EGFP, the protein product of which is identifiable 4-6 hours following viral entry into cells. While green fluorescent protein and its derivative proteins have been used extensively as reporters and/or markers in numerous biologic studies (60)(61)(62)(63)(64)(65), their use to determine infection and spread of replication-competent viral vectors in vivo is an emerging technology. Previous studies have demonstrated that the fluorescent signal from cells constitutively expressing GFP correlates strongly with cell number in vitro (66).…”
Section: Discussionmentioning
confidence: 99%